Implementación de nuevos potreros de ganado vacuno a través de un proceso de optimización logística y de espacio - Campozano, J. (2009)
The project bases on satisfying the needs of the cattle ranch El Tejano that unwraps one with a normal production, but without growth being kept constant in the time. The objective is: Use the land in efficient way, optimize the process of production, and increase the meat production to cover the sales quotas with his fixed customers. Our proposal is to implement a livestock register system where one sees reflected the main ones give birth. Our proposal is to implement a livestock register system where one sees reflected the main parameters of the meat production rancher and so be able to evaluate the cluster correctly. To achieve our objectives, we will build new pastures enlarging like that our workspace, to reorganize the livestock per age and condition, in the underutilized hectares of the livestock El Tejano. We will change the food to intensive and rotational, causing less floor wear and maximum grass use. Improving so the times of livestock fattening from 3 to 1.5 years we will increment by a 17% the sales from 3er year, This way during two first years of the project income by sale will not be generated because he tries to increment the livestock head population from third year we are in capacity of starting to sell animal. After having reached a level of births and percentages of pregnancy that help us to keep the cluster production to constant levels for to cover the sales quotas.